2008
DOI: 10.1007/s00280-008-0740-8
|View full text |Cite
|
Sign up to set email alerts
|

NSC606985, a novel camptothecin analog, induces apoptosis and growth arrest in prostate tumor cells

Abstract: Purpose-Prostate cancer is a major cause of cancer mortality in American males. Once prostate cancer has metastasized, there is currently no curative therapy available. The development of effective agents is therefore a continuing effort to combat this disease. In the present study, the effects and potential mechanisms of NSC606985 (NSC), a water-soluble camptothecin analog, in prostate cancer cells were investigated.Methods-Prostatic tumor cells, DU-145, LNCaP and PC-3, were used for the study. Cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…CPT is known to exert killing effects by inducing apoptosis in cancer cells (Tan et al, 2009). To reveal whether miR-125b was involved in CPT-induced apoptosis, we investigated the expression patterns of miR-125b during apoptotic stress after CPT treatment.…”
Section: Mir-125bmentioning
confidence: 99%
See 1 more Smart Citation
“…CPT is known to exert killing effects by inducing apoptosis in cancer cells (Tan et al, 2009). To reveal whether miR-125b was involved in CPT-induced apoptosis, we investigated the expression patterns of miR-125b during apoptotic stress after CPT treatment.…”
Section: Mir-125bmentioning
confidence: 99%
“…One of the major modes of action of these chemotherapeutic drugs may be via the activation of apoptosis (Makin and Dive, 2001). Indeed, several researchers have reported that CPT induces apoptosis in various cancer cells (Sá nchez-Alcá zar et al, 2000;Tan et al, 2009). However, the detailed molecular mechanisms are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…To measure gene expression, RT-PCR and real-time PCR were performed as previously described (15,24). Briefly, total cellular RNA was isolated using TriPure reagents, and the level of specified RNAs were quantified using a NanoDrop2000C.…”
Section: Reverse Transcription Pcr (Rt-pcr) and Quantitative Rt-pcrmentioning
confidence: 99%
“…Western blotting was carried out following standard methods with minor modifications (15). Briefly, cells were harvested and total cellular proteins were extracted using a RIPA buffer (25 mM Tris-HCl pH 7.6, 150 mM NaCI, 1% NP-40, 1% sodium deoxycholate, 0.1% SDS).…”
Section: Reverse Transcription Pcr (Rt-pcr) and Quantitative Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation